RECOVERY OF SODIUM FROM ALUMINA-EXTRACTED FLY ASH USING CONCENTRATED SODIUM CARBONATE SOLUTION - Wang, Zehua; Zheng, Shili; Ma, Shuhua; Ding, Jian; Wang, Xiaohui (Journal of Mining and Metallurgy, Section B: Metallurgy, 2018)
A novel method for recovery of sodium from alumina-extracted fly ash (AEFA), which was mainly composed of NaCaHSiO4, using concentrated Na2CO3 solution was presented. Sodium was extracted from the AEFA efficiently, and the factors influencing the process were systematically investigated. The optimal conditions were as follows: reaction temperature = 180 °C, Na2CO3 concentration = 170 g/L, liquid-to-solid ratio = 10 mL/g, and reaction time = 2 h. Under optimal conditions, the Na2O extraction rate was 93.79%, and the Na2O content of the products was 1. 02 wt% which was lower than that of the products obtained from the recovery of sodium from AEFA in a dilute NaOH solution (i.e., 2 wt%). Furthermore, this process avoided the production of a dilute NaOH solution, thus lowering the energy consumption during concentrating and recycling the recovered sodium when compared with the NaOH-based route. Therefore, the recovery of sodium from AEFA using concentrated Na2CO3 solution was more suitable for use in industrial applications. In addition, the 27Al MAS NMR result revealed that the residual Na+ ions are adsorbed to compensate for the charge deficit due to the replacement of Si4+ by Al3+ ions in the tobermorite structure.